2020
DOI: 10.1155/2020/2584627
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Molecular Evolution of AKT3 Gene for Positive Diversifying Selection in Mammals

Abstract: The V-Akt Murine Thymoma Viral Oncogene Homolog 3 (AKT3) gene is of the serine/threonine-protein kinase family and influences the production of milk fats and cholesterol by acting on the sterol administrative area restricting protein (SREBP). The AKT3 gene is highly preserved in animals, and during lactation in cattle, its expression increases. The AKT3 gene is expressed in the digestive system, mammary gland, and immune cells. A phylogenetic investigation was performed to clarify the evolutionary role of AKT3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Coincidentally, DAXX was identified as a CDG for the lumbar muscle area and lumbar muscle depth in Duroc pigs [ 15 ]. Some studies found that AKT3 is one of the CDGs for the number of nipples and promotes milk fat production of mammals such as cattle [ 35 , 36 ]. AKT3 is also involved in various biological functions, including inflammatory response, lipolysis metabolism, and muscle fiber characteristics [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Coincidentally, DAXX was identified as a CDG for the lumbar muscle area and lumbar muscle depth in Duroc pigs [ 15 ]. Some studies found that AKT3 is one of the CDGs for the number of nipples and promotes milk fat production of mammals such as cattle [ 35 , 36 ]. AKT3 is also involved in various biological functions, including inflammatory response, lipolysis metabolism, and muscle fiber characteristics [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Siah1 has recently been identified as an upstream regulator of Akt3 (Akt signaling is an important regulator of neural development) (133)(134)(135), and it is responsible for the ubiquitination and degradation of Akt3, suggesting that Siah1 may play a key role in neural development (135).…”
Section: Siah1 In Nervous System Diseasesmentioning
confidence: 99%